Flavonol Glycosides from Leaves of Bergenia himalaica - Hasan, Aurangzeb; Hussain, Ajaj; Ajab Khan, Mir (Asian Journal of Chemistry, 2016)
A new flavonol triglycosides, quercetin 3-O-a-L-rhamnopyranosyl (1®2)-b-D-galcatopyranosyl (1®6)-b-D-glucopyranoside (1) was isolated from the leaves of Bergenia himalaica together with three known flavonol diglycosides: kaempferol-3-O-a-L-rhamnopyranosyl-7-O-a-L-arabinopyranoside (2), quercetin-3-O-b-D-xylopyranosyl (1®6)-b-D-glucopyranoside (3), quercetin-3-O-a-L-arabinopyranosyl (1®2)-b-D-glucopyranoside (4) and five known flavonol monoglycosides: kaempferol-7-O-a-L-rhamnopyranoside (5), kaempferol-7-O-b-D-allopyransoide (6), quercetin-3-O-b-D-xylopyranoside (7), quercetin-3-O-b-D-gluco-pyranoside (8) and quercetin-3-O-a-L-rhmnopyranoside (9). Their structures were determined on the basis of Rf values, acid hydrolysis, UV-Visible EIMS, FAB+ MS, 1H and 13CNMR spectral data.